Job Uncertainty and The Well-Being of Non-Permanent Employees - Lawolo, Marniaman; Waruwu, Eliyunus; Mendrofa, Syah Abadi; Waruwu, Meiman H. (Manunggal Halim Jaya, 2024)
This research aims to analyze the influence of job uncertainty on the motivation and performance of non-permanent employees at the Nias Regency DPRD Secretariat, identify effective HR management strategies in reducing the negative impact of job uncertainty on the welfare of non-permanent employees, and assess the role of managerial support and the work environment in mitigating the effects. negative job uncertainty on the welfare of non-permanent employees. This research uses qualitative research methods using observation, interview and documentation data collection techniques. The research results show that job uncertainty is mainly caused by inconsistent contract policies, frequent regulatory changes, and a lack of effective communication from management. The impact of this uncertainty is very significant, especially on employees' psychological well-being, which includes increased levels of stress, anxiety, as well as decreased work motivation and productivity. To overcome this problem, this research proposes several policy recommendations, including the need for more consistent contract policies, a more transparent communication system, and additional welfare support for employees. By implementing these recommendations, it is hoped that the Nias Regency DPRD Secretariat can create a more stable work environment, improve employee welfare, and support the long-term success of the organization.